High-Speed Optical Wireless Demonstrators: Conclusions and Future Directions - O'Brien, D; Turnbull, R; Le Minh, H; Faulkner, G; Bouchet, O; Porcon, P; El Tabach, M; Gueutier, E; Wolf, M; Grobe, L; Li, J (2012)
Two high-speed angle diversity optical wireless systems have recently been implemented, as part of a European Community funded project. One operates at 1.25 Gb/s offering a limited coverage area, and the other at 280 Mb/s, with room scale coverage. In this paper, we summarize the design approach for these systems and their performance. Implications of these results for the design and implementation of future systems are also discussed. © 2012 IEEE.